Hubungan Faktor Pelayanan Internal Kefarmasian Dengan Tingkat Kepuasan Orangtua Pasien Di Rumah Sakit Aisyiyah Siti Fatimah - TJATUR PRIJAMBODO; MUSA GHUFRON; YELVI LEVANI; SISKA MAWADDATUNNADILA (Universitas Hang Tuah, 2021)
Abstract Background: Adequate health and well-being is a human right that has been recognized throughout the world. Indonesia has agreed to this as evidenced by the existence of Law No.36 of 2009. Hospital is one of the public health services that has pharmaceutical installation facilities, outpatient care, and so on. Objective: To determine the characteristics of pediatric specialist clinic patients and to determine the relationship between internal pharmaceutical service factors and the satisfaction level of pediatric specialist clinic patients at Aisyiyah Siti Fatimah Tulangan Hospital. Methods: This study is a descriptive analytic study with a cross sectional approach. The technique used is total sampling. The sample size was taken from all parents of pediatric specialist clinic patients who took medicine at the Pharmacy Installation at Aisyiyah Siti Fatimah Tulangan Hospital and met the inclusion criteria. The instrument used was satisfaction questionnaire that was collected from November to December 2019. The data obtained in this study were analyzed using the Chi Square method. Results: Based on the Chi Square test between Human Resources, Medicine, and Process, it shows p> 0.05, so there is no significant correlation between these variables and patient satisfaction. The results of the Chi Square test between the facilities and infrastructure variables showed p <0.05, which means that there is a significant correlation between the variable facilities and infrastructure for the pharmaceutical installation of Aisyiyah Siti Fatimah Tulangan Hospital and patient satisfaction. Conclusion: Internal service factor of pharmacy that has influence is infrastructure, while other factors in the form of human resources and processes have no relationship